UPAYA THE MILLENIUM CHALLENGE CORPORATION (MCC) MENGATASI PENYEBARAN CAMPAK DI TIMOR-LESTE - da Silva, Jenifer Olivia; Rainy Priadarsini, Ni Wayan; Widya Nugraha, A.A. Bagus Surya (Program Studi Hubungan Internasional FISIP Universitas Udayana, 2020)
ABSTRACT The problem of immunization coverage in Timor-Leste is among the poorest in Asia. In 2009/2010 the Demographic and Health Survey found that immunization coverage for Timor-Leste was only 68.2% for Measles. In line with the commitment of the Timor-Leste government is to increase the coverage of vaccination in Timor-Leste, the involvement of MCC through the Threshold program was highly expected to help realize the goals of the Timor-Leste government. MCC forms a Threshold program, and a grant program designed for developing countries with a period of 3 years. This study aims to describe the efforts of the MCC through the Threshold program in preventing measles in Timor-Leste. This study assessed by using the concept of development aid and community empowerment. The locus of this study is from 2011 to 2013. Keywords: measles, Timor-Leste, MCC, Threshold Program